(untitled) (Journal of Mechanical Engineering, 2010)
The paper presents the results of numerical calculations for filmwise condensation of downward flowing pure saturated steam on a horizontal tube. A tube of 19.05 mm diameter was used. Steam approach conditions used were 5000 N/m2 (Tsat = 32.9 oC) pressure and velocity 5 – 100 m/s. Tube wall temperatures were considered to be constant at 22.9 oC and 30.9 oC, giving condensate subcooling DT = 10 K and 2 K respectively. Earlier theoretical studies omitted the variations of physical properties with pressure arising from flow of vapor over the tube surface. The present work takes into account these property variations. The velocity and pressure distributions were taken from the potential flow theory. At low condensate subcooling, DT = 2 K, and high steam velocities, significant reduction of average heat transfer coefficient was predicted when property variations were taken into account, compared to constant property values. The mean heat flux predicted considering the variation of properties was up to 9% and 42% less than that obtained for DT = 10 K and 2 K respectively. Keywords: Laminar filmwise condensation; horizontal tube; boundary layer separation; numerical. DOI: 10.3329/jme.v40i2.5347 Journal of Mechanical Engineering, Vol. ME 40, No. 2, December 2009 79-89